Persepsi Terhadap Digitalisasi Akuntansi dalam Era Industri 4.0 pada KSP Sumekar Yogyakarta - Henny, Henny (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the perceptions of the management and members of KSP Sumekar Yogyakarta regarding the digitalization of accounting in their daily operational activities, especially for inventory control and financial information in this industrial era 4.0. In this study, the author uses the Technology Accepted Model (TAM) theory because by using this theory, the most appropriate and best concept can be obtained to explain user perceptions in accepting new technology in their field of work. In this study, the author used a population of all administrators and members of KSP Sumekar Yogyakarta, totaling 45 (forty-five) people, using the census method. The results of the study prove that of the total of 5 (five) accepted hypotheses, 4 (four) hypotheses are: the influence of Perceived Ease of Use (PEOU) on Perceived Usefulness (PU), the influence of Perceived Ease of Use (PEOU) on the perception of Attitude Toward Using (ATT), the influence of Perceived Usefulness (PU) on Acceptance of Information Technology (ACIT), and the influence of Attitude Toward Using (ATT) on Acceptance of Information Technology (ACIT). So the results of this study show that employee perceptions of the use of accounting digitalization can be explained using the Technology Acceptance Model (TAM) theory.